Soviet and Buddhist: religious diplomacy, dissidence, and the Atheist State, 1945-1991 - Sablin, Ivan (The journal of religion, 2019)
The article offers information Soviet Buryatia that symbolized the failure of Soviet efforts to remove religion. It mentions that the return of Buddhism to the public life of the USSR after the antireligious campaign of 1928-1940 has not been initiated by the Perestroika and Glastnost campaigns. It mentions that Buddhism had never been officially outlawed in the USSR.
Keywords: Geschichte 1945-1991; Buddhismus; Atheismus; Sowjetunion